Creativity Environment on Arabic-Language-Learning of Junior High School Based-on The Development of Merdeka Curriculum - Nur Alisya Ahda Sabila; Inayah Inayah; Waesama-ae Waemamu (Lughawiyah: Journal of Arabic Education and Linguistics, 2026)
This study highlights the application of a creativity-oriented learning environment in the Arabic Language Learning (ALL) process at the Junior High School level, developed in line with the principles of the Merdeka Curriculum. The background of this study is the urgent need for a transformation in learning centered on students. It promotes strengthening essential 21st-century skills, such as critical thinking, collaboration, creativity, and communication. Through explanatory qualitative research methods, this study examines how project-based learning methods and relevant digital technologies are applied to optimize students’ proficiency in four aspects of language: listening, speaking, reading, and writing in Arabic. The research findings show that an innovative learning atmosphere can stimulate active student participation through interactive games, digital tasks, and role-playing activities. This makes the learning process more memorable and enjoyable. The Merdeka Curriculum also allows educators to integrate character development through the P5 program without neglecting learning objectives. Despite challenges such as insufficient teacher readiness and limited digital facilities, this study demonstrates that creative methods can enhance the validity of Arabic language Learning. These findings reinforce the shift towards active, interactive, and competency-focused learning.